Design and construction of a mosquito trap using DC high voltage using the Cockcroft-Walton method - Suriyanto, S; Rosdiana, R (Journal Geuthee of Engineering and Energy, 2023)
The tropical climate in Indonesia is very helpful in breeding mosquitoes everywhere, the Aedes aegypti mosquito is the main cause of the spread of dengue fever in Indonesia. Mosquitoes' hexagonal eyes make them attracted to light, UV light with a wavelength between 350 nm and 370 nm is what can attract insects. The use of high voltage is felt to be more effective in killing mosquitoes. This research aims to find out at what time, temperature and air humidity how many mosquitoes come out to suck blood from both humans and animals. And find out at what DC voltage mosquitoes die from being stung. The device design includes UV LED, Temperature Sensor, and High Voltage DC (HVDC). UV LEDs are used as mosquito attractants, because mosquitoes like ultraviolet light, temperature also affects mosquito activity. At temperatures that are too cold, mosquitoes don't leave the nest much, and if it's too hot, the DHT11 sensor is used as a temperature gauge on the tool so that the tool works. High voltage is used to kill mosquitoes by applying voltage to the positive and negative wires, so that trapped mosquitoes will be stung to death. From the experimental results obtained, mosquitoes began to fly actively when sunset arrived, because the temperature and humidity levels were at the warm level that mosquitoes like. And mosquitoes will die if they are shocked by a voltage with a minimum value of 280V to a higher DC voltage.